Determination of Elastic and Mechanical Properties in CA-50 Steel by using Ultrasonic Waves - Carvalho Júnior, Álvaro Barbosa de; Lopes, Maria Helena Teles; Inácio, Maurílio José; Ramos, Samara Guedes; Rodrigues, Debora Santos; Froes, Gustavo Dias; Botelho Fonseca, Vinícius Marques; de Oliveira, Jairo Andrei Vieira (International Journal of Advanced Engineering Research and Science, 2022)
The aim of this study was to characterize the elastic and mechanical properties of CA-50 steel using the ultrasonic through-transmission technique. The electronic system used is composed of piezoelectric transducers, one emitter and another receiver of ultrasonic waves with 2 MHz frequency. Elastic properties such as Young’s modulus, shear, bulk, Poisson's ratio and anisotropy factor were estimated. In order, to estimate the mechanical properties, one mathematical model proposed in the literature was used, which related the longitudinal ultrasonic velocity with the values of tensile strength. The results obtained were compared with reference values found, attesting the feasibility of low-cost method to investigate carbon steels.